2005
DOI: 10.1016/j.jce.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy rules for Russia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 15 publications
0
16
1
2
Order By: Relevance
“…The results displayed in Figure 2a show that a positive interest rate shock leads to (i) a strong and persistent contractionary effect on GDP; (ii) a fall in the price of raw materials; (iii) an appreciation of the exchange rate; and (iv) a negative and persistent effect on the equity markets, which reach a trough of −10% after two quarters. Esanov, Merkl, and Vinhas de Souza (2005) show that, during the period 1993-2002, the Bank of Russia used monetary aggregates as a main policy instrument in conducting monetary policy. 1 The impulse-response functions of Figure 2b roughly "mirror" the ones in Figure 2a.…”
Section: The B-svar Frameworkmentioning
confidence: 99%
“…The results displayed in Figure 2a show that a positive interest rate shock leads to (i) a strong and persistent contractionary effect on GDP; (ii) a fall in the price of raw materials; (iii) an appreciation of the exchange rate; and (iv) a negative and persistent effect on the equity markets, which reach a trough of −10% after two quarters. Esanov, Merkl, and Vinhas de Souza (2005) show that, during the period 1993-2002, the Bank of Russia used monetary aggregates as a main policy instrument in conducting monetary policy. 1 The impulse-response functions of Figure 2b roughly "mirror" the ones in Figure 2a.…”
Section: The B-svar Frameworkmentioning
confidence: 99%
“…At the same time, a stimulating monetary policy causes a drop in the national currency's exchange rate, which also helps to increase prices. But, as a number of studies have shown, 15 the exchange rate is one target of the central bank's monetary policy. Thus, monetary policy is endogenous in relation to the exchange rate and, following economic theory, needs to be taken into account when estimating pass-through.…”
Section: Analysis Of Exchange Rate Pass-through To the Aggregated Conmentioning
confidence: 99%
“…Moreover, a stimulating monetary policy causes a drop in the Russian rouble. Meaning that monetary policy is endogenous in relation to the rouble, as demonstrated by previous studies, see [7]. Using a three variables model, [8] get interested in effects induced by the switch to a floating exchange rate of rouble in November 2015.…”
mentioning
confidence: 97%